14C Dating of the Roman Military Interventions in the Middle Danube Barbarian World. Issue 2 (31st October 2018) - Komoróczy, Balázs; Vlach, Marek; Hüssen, Claus-Michael; Rajtár, Ján
ABSTRACT: The Roman-barbarian interactions along the riverine borderline of the Middle Danube Limes exhibit a wide range of forms, from peaceful contacts and trading activities to full-scale military conflicts. The direct evidence of the latter type of events represents a specific source of archaeological information—generally referred to as temporary camps. The regions of Moravia, SW Slovakia and Lower Austria currently encompass more than 30 verified Roman military field installations. The specifics of these archaeological contexts and the present unsatisfactory state of knowledge have raised the necessity of approaching the given questions with advanced techniques, not least with respect to their chronological position. Along with multiple methods and analytical procedures of relevant natural sciences (geophysics and geochemistry, archaeobotany, microstratigraphy, etc.), radiocarbon ( 14 C) dating has also been involved in order to further establish the chronological position of temporary camps because the archaeological data provide limited possibilities in this respect. In multiple cases, the method has augmented traditional dating techniques and allowed more precise and secure establishment of the chronological position of the field camps of the Roman army.